STELLAR ACTIVITY CYCLES: WHY DO WE NEED IN THE LONG-TERM MEASUREMENTS OF THE MAGNETIC FIELD? - Plachinda, S. I.; Butkovskaya, V. V. (Одеські астрономічні публікації, 2017)
Solution of the two important problems requires a study of long-term behavior of the magnetic ﬁeld on stars with nondegenerate matter: ﬁrstly, to deﬁne the role of the magnetic ﬁeld on diﬀerent evolutionary stages of stars; secondly, to know the inﬂuence of the star’s activity on space weather in the habitable zone. This brief review summarizes the ﬁrst results of the long-term magnetic ﬁeld measurements on selected stars.